Genes that encodes NAGT, MIF1 and MIF2 are not virulence factors for kala-azar caused by Leishmania infantum - Aguiar, Bruno Guedes Alcoforado; Coelho, Daniela Lemos; Costa, Dorcas Lamounier; Drumond, Betânia Paiva; Coelho, Luiz Felipe Leomil; Figueiredo, Lívio Carvalho; Zacarias, Danielle Alves; Silva, Jailthon Carlos Da; Alonso, Diego Peres [UNESP]; Ribolla, Paulo Eduardo Martins; Ishikawa, Edna Aoba Yassui; Gaído, Samara Belchior; et al. (Sociedade Brasileira de Medicina Tropical - SBMT, 2014)
Introduction Kala-azar is a disease resulting from infection by Leishmania donovani and Leishmania infantum. Most patients with the disease exhibit prolonged fever, wasting, anemia and hepatosplenomegaly without complications. However, some patients develop severe disease with hemorrhagic manifestations, bacterial infections, jaundice, and edema dyspnea, among other symptoms, followed by death. Among the parasite molecules that might influence the disease severity are the macrophage migration inhibitory factor-like proteins (MIF1 and MIF2) and N-acetylglucosamine-1-phosphotransferase (NAGT), which act in the first step of protein N-glycosylation. This study aimed to determine whether MIF1, MIF2 and NAGT are virulence factors for severe kala-azar. Methods To determine the parasite genotype in kala-azar patients from Northeastern Brazil, we sequenced the NAGT genes of L. infantum from 68 patients as well as the MIF1 and MIF2 genes from 76 different subjects with diverse clinical manifestations. After polymerase chain reaction (PCR), the fragments were sequenced, followed by polymorphism identification. Results The nucleotide sequencing of the 144 amplicons revealed the absence of genetic variability of the NAGT, MIF1 and MIF2 genes between the isolates. The conservation of these genes suggests that the clinical variability of kala-azar does not depend upon these genes. Additionally, this conservation suggests that these genes may be critical for parasite survival. Conclusions NAGT, MIF1 and MIF2 do not alter the severity of kala-azar. NAGT, MIF1 and MIF2 are highly conserved among different isolates of identical species and exhibit potential for use in phylogenetic inferences or molecular diagnosis.
Keywords: Genetic diversity; Kala-azar; Visceral leishmaniasis; Macrophage inhibition factor; Tropical diseases; Single nucleotide polymorphism